Evaluating the Impact of Non-Financial IMF Programs Using the Synthetic Control Method - Newiak, Monique; Willems, Tim. (Washington, D.C. : International Monetary Fund, 2017)
We use the Synthetic Control Method to study the effect of IMF advice on economic growth, inflation, and investment. The analysis exploits the existence of IMF programs that do not involve any financing (Policy Support Instruments, 'PSIs'). This enables us to focus on the effects of IMF monitoring, advice, and approval (as opposed to direct financial assistance). In addition, countries with non-financial programs are typically not crisis-struck - thereby mitigating the reverse causality problem and facilitating the construction of counterfactuals. Results suggest that treated countries add about 1 percentage point in annual real GDP per capita growth, with inflation being lower by some 3 percentage points per year. While we do not find evidence for an impact on total investment and the resulting capital stock, PSI-treatment does seem to stimulate foreign direct investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Cabo Verde